2022
DOI: 10.3390/ijerph192315569
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Work-Related Mental Health in 2017 and 2020—A Comparative Follow-Up Study before and during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic put a lot of strain on healthcare organizations. Nurses account for over 50% of healthcare staff, and how nurses perform in their work is influenced by a number of human and work environmental factors. However, to our knowledge, there has not been a previous study with the intention to look at all areas that affect a sustainable working life and how these impact nurses’ mental well-being. The aim of this study is to investigate the association between, and the effect of, different factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A sustainable working life was stressed by the effects of the COVID-19 pandemic on working life and the work environment. Nagel and Nilsson [16] used a questionnaire to investigate the association between, and the effect of, different factors in nurses' work situations, organised based on the SwAge-model theories of a sustainable working life, associated with nurses' work-related mental health diagnoses, before and during the COVID-19 pandemic. The results showed that lack of joy in the daily work, an increased workload, and lack of support from co-workers had an increased association with work-related mental health diagnoses.…”
Section: Conclusion Of the New Knowledgementioning
confidence: 99%
“…A sustainable working life was stressed by the effects of the COVID-19 pandemic on working life and the work environment. Nagel and Nilsson [16] used a questionnaire to investigate the association between, and the effect of, different factors in nurses' work situations, organised based on the SwAge-model theories of a sustainable working life, associated with nurses' work-related mental health diagnoses, before and during the COVID-19 pandemic. The results showed that lack of joy in the daily work, an increased workload, and lack of support from co-workers had an increased association with work-related mental health diagnoses.…”
Section: Conclusion Of the New Knowledgementioning
confidence: 99%
“…At the same time the shortage of nurses in Europe is so serious that it has been described as "a ticking time bomb" [7], especially in the case of specialised nurses [8], which is furthermore aggravated by the trend of nurses' motivation to leave the profession and workplace [9][10][11][12][13][14][15]. It is therefore essential to not only avoid burnout [13,16], depression [17], and mental health problems among nurses [18], but also identify resistance resources against stress [19,20], enhancing resources for health [21], work-related "push and pull factors" [11], and even factors that make nurses thrive professionally [22,23], enabling nurses to remain in the profession and workplace.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time the shortage of nurses in Europe is so serious that it has been described as "a ticking time bomb" [7], especially in the case of specialised nurses [8], which furthermore is aggravated by the trend of nurses' motivation to leave the profession and workplace [9][10][11][12][13][14][15]. It is therefore essential to not only avoid burnout [13,16], depression [17] and mental health problems among nurses [18], but to identify resistance resources against stress [19,20], enhancing resources for health [21], work-related "push and pull factors" [11], and even factors that make nurses thrive professionally [22,23], that would enable nurses to remain in the profession and workplace.…”
Section: Introductionmentioning
confidence: 99%